ECONOMIC EVALUATION OF PLANTATIONS OF BOLAINA BLANCA (Guazuma crinita Mart.) IN UCAYALI, PERU - REVILLA-CHÁVEZ, Jorge Manuel (2022)
Between 2001 and 2006, demostrative plantations of bolaina blanca (Gauzuma crinita Mart.) were evaluated in three sectors of the Aguaytı́a river basin that had as previous use cassava crop, 3‑year purma and corn crop in sectors 1, 2 and 3 respectively. Using predictive models of volume and biomass in function of the plantation age, we determined the technical‑economic viability of plantations in a six‑years‑old scenario of sale of slats, tucos and cantoneras (goods) and capture of CO2eq (services) updated to the year 2022 with anannual effective rate of return of 22%. They had a net present value (NPV), internal rate of return (IRR), and benefit/cost ratio (B/C) of S/. 8 408,67; 60,9% and 1,58 for sector 3; S/. 967,23; 26,5% and 1,07 for sector 2; and S/. ‑7945,28; 0,0% and 0,14 for sector 1, which were mainly influenced by income generated by the sale of wood chips and the sale of positive flows of carbon sequestration services resulting from the establishment of plantations in soils where the previous use was an annual crop. Thus, the plantation in sectors 3 and 2 were technically and economically viable, while the plantations in sector 1 were not.